Дослідження завадостійкості систем радіозв’язку MC-CDMA при використанні неповних ансамблів послідовностей - Михайленич, П. М. (Проблеми телекомунікацій, 2012)
The methods of MC-CDMA signals generation, receiving and signal transmission simulation over AWGN, Raleigh channels considered in this paper. The research of bit error rate performance during data transmission conducted.
Keywords: CDMA; OFDM; MC-CDMA; канал зв’язку